2016
DOI: 10.7567/jjap.55.056201
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of hollow cathode discharge electrode for damage free remote plasma removal process for semiconductor manufacturing

Abstract: Cone-shaped hollow cathode electrode configuration for a damage free remote plasma removal process has been optimized for given pressures based on Paschen characteristic curves, voltage–current characteristics and time-resolved discharge observations as well as oxide film removal performances. Remote plasmas have been generated in two types of cone-shaped electrodes with mixtures of He, NF3, and NH3 for pressure range of 1–30 Torr. Paschen characteristic curves and voltage–current (V–I) characteristics define … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The observed discharge characteristics in figure 4 are in agreement with earlier experimental reports, which showed higher ionization and power deposition inside conical cathode than a cylindrical cathode system [5][6][7]. The frontal and the lateral images of the plasma column from each HC setup is shown in figure 4(c).…”
Section: Discharge Characteristics Of Cylindrical and Conical Hc Plas...supporting
confidence: 89%
See 2 more Smart Citations
“…The observed discharge characteristics in figure 4 are in agreement with earlier experimental reports, which showed higher ionization and power deposition inside conical cathode than a cylindrical cathode system [5][6][7]. The frontal and the lateral images of the plasma column from each HC setup is shown in figure 4(c).…”
Section: Discharge Characteristics Of Cylindrical and Conical Hc Plas...supporting
confidence: 89%
“…, where ν iz is the frequency of ionization. Considering that ions are un-magnetized in the system, the ion momentum equation reduces to equation (6), where M is the ion mass, e is the electron charge and E is the local electric field inside the plasma volume. The radial component of this electric field can be derived from the plasma potential f by = -…”
Section: Charge Particle Equilibrium Across the Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of a corrosion inhibitor ( i.e., BTA) controls the static dissolution via the formation of complexes that modulate the rate of oxidation from Cu(0) to Cu(I) to Cu(II). 13,31,32 Commonly, the incorporation of BTA will form a polymeric film via Cu(I) coordination on the surface of a Cu substrate resulting in an interactive but dense passivation film. 33 It has been reported that the BTA film forms in a two-stage process consisting of BTA surface adsorption and subsequent complexation with the oxidized Cu(I) species (logβ = 1.54 × 10 −2 ) at the interface.…”
Section: Resultsmentioning
confidence: 99%
“…A (NH 4 ) 2 SiF 6 -based modified layer forms on the surface of SiO 2 when it is exposed to etchants such as NH 3 =NF 3 -based or HF=NH 3based chemistry. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] These chemistries were commercialized in the semiconductor industry for use in precleaning technologies in film deposition, silicidation, and the fabrication of high-k dielectric metal gates. [29][30][31][32][33] Very recently, the thermal cyclic etching of SiN has also been realized.…”
Section: Advances In Atomic Layer Processing For Emerging Materialsmentioning
confidence: 99%